2021
DOI: 10.1155/2021/2649123
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Transcription Factor Signature That Can Predict Breast Cancer Survival

Abstract: Background. The expression pattern of transcription factors (TFs) can be used to develop potential prognostic biomarkers for cancer. In this study, we aimed to identify and validate a TF signature for predicting disease-free survival (DFS) of breast cancer (BRCA) patients. Methods. Lasso and the Cox regression analyses were applied to construct a TF signature based on a gene expression dataset from TCGA. The prognosis value of the TF signature was investigated in the TCGA database, and its reliability was furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Subsequently, a prognostic model consisting of 6-DEDGs was constructed by univariate Cox regression and LASSO Cox regression analysis. The model had better predictive capability for BRCA's survival compared to previous prognostic genetic models (AUC = 0.5-0.6) [29,30], especially in the 5-year survival rate (AUC = 0.701). The AUC value is proportional to the model's predictive performance, and AUC greater than 0.7 means higher predictive ability [8].…”
Section: Discussionmentioning
confidence: 80%
“…Subsequently, a prognostic model consisting of 6-DEDGs was constructed by univariate Cox regression and LASSO Cox regression analysis. The model had better predictive capability for BRCA's survival compared to previous prognostic genetic models (AUC = 0.5-0.6) [29,30], especially in the 5-year survival rate (AUC = 0.701). The AUC value is proportional to the model's predictive performance, and AUC greater than 0.7 means higher predictive ability [8].…”
Section: Discussionmentioning
confidence: 80%
“…In our study, the immune infiltration analysis showed that monocytes were associated with a good prognosis, while the opposite was true for resting memory CD4 T cells, in line with previous studies [ 39 ]. In addition, previous studies have also revealed that the M2 macrophages confer dismal prognosis in gliomas [ 40 ] and other types of tumors [ 41 ]. The mechanistic roles of macrophages in cancer progression have been summarized elsewhere [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…TFs may serve as biomarkers to predict the prognosis of BRCA (23,24). Several TF-related signatures have been reported to predict the clinical outcomes of many cancers (19,(25)(26)(27); however, few studies have focused on TF-related signatures that can predict OS in BRCA. In our study, we established and validated a 9-TF signature risk model that could predict OS in BRCA via a comprehensive analysis of TF data.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have developed a microRNA (miRNA) -based signature for BRCA (17) and an immunerelated long non-coding RNAs (lncRNAs) prognostic signature for TNBC (18), which provided the basis for predicting prognosis. Another study identified a novel prognostic TF signature for predicting disease-free survival (DFS) of BRCA patients (19). Nevertheless, only a few studies have systematically investigated the expression pattern, potential mechanism, and prognostic ability of TFs in BRCA.…”
Section: Introductionmentioning
confidence: 99%